2023
DOI: 10.1186/s12910-023-00884-2
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented understanding: exploring the practice and meaning of informed consent in clinical trials in Ho Chi Minh City, Vietnam

Abstract: Background The informed consent process in clinical trials has been extensively studied to inform the development processes which protect research participants and encourage their autonomy. However, ensuring a meaningful informed consent process is still of great concern in many research settings due to its complexity in practice and interwined socio-cultural factors. Objectives This study explored the practices and meaning of the informed consent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Consequently, this affects patient assessments and care [ 25 ]. Similarly, a study conducted in Vietnam showed that differences in social and cultural factors can shape the practices of informed consent and result in a fragmented understanding of information [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this affects patient assessments and care [ 25 ]. Similarly, a study conducted in Vietnam showed that differences in social and cultural factors can shape the practices of informed consent and result in a fragmented understanding of information [ 26 ].…”
Section: Discussionmentioning
confidence: 99%